The Importance of Intangible Reward in English Language Learning - Alfat, Ayu Ariska; Que, Stella Rose (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2022)
Intangible rewards are an award that is crucial to the students to perform outrages performance so that they can get appreciation. Intangible reward refers to a class of rewards which have no material or monetary value but can keep the students feeling recognized and motivated. Intangible reward is not specifically researched in the teaching profession. It has been linked since human beings have the same psychological experience in terms of pursuing better achievement both in academic and work fields. It is proven that intangible rewards provide continual treatment to help students stay motivated and energized. Using library research, this study tries to explore the positive impact of intangible rewards on the students. It focuses on discussing how intangible rewards as literary works in the EFL context affects students’ language learning. Based on the literary review and the writer's experience at the English Education Study Program, the advantages that the students get by receiving intangible rewards, specifically in improving their language skills, is work. Intangible rewards do improve students’ language skills.